Straight Talk To MEN and Their Wives - Dobson, James C. (Waco Word Books, 1980)
Discusses what it means to be a man; how a man should relate to his wife, his children, his work, and his God; and how a wife can understand and be supportive.
Keywords: Men -- United States. Fathers -- United States. Men -- Psychology. Men -- Religious aspects -- Christianity. Fathers. Men. United States